Hygienic assessment of water quality and safety according to national requirements - I. I. Panikar; V. O. Rud; N. Vartik (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
There are only 15 % of water reservoirs in Ukraine that can be used as sources of water supply, taking into account water treatment facilities. 55 % of polluted objects and 30 % very dirty, water from these sources cannot be used even after cleaning. With the help of sanitary-hygienic, ecological and water management assessment, they ensure the quality of water in the impact on the environment and the quality of fish products. The main documents that determine the quality, properties and chemical composition of drinking water are DSTU 7525:2014 and DSTU 27384:2005, they specify the main toxicological and organoleptic concentrations of chemicals that must be contained in water. The standard “Sources of centralized economic drinking water supply, hygienic and ecological requirements for water quality and selection rules” makes it possible to develop a complex of interrelated standards and norms, including the use, protection and restoration of water resources, objective assessment of the ecological state and quality of surface and underground waters and their compliance with the requirements of EU standards. Water treatment equipment and technologies used nowadays for wastewater treatment do not provide a sufficient degree of purification and disinfection. Surface water reservoirs, along with impurities of natural origin, contain chemical pollution – heavy metals, pesticides, insecticides, oil products, phenols. The methods of wastewater disinfection are divided into chemical, physical, physico-chemical and in the conditions of artificial and natural biocenoses.